Mandibular adenomatoid odontogenic tumor: case report - Bali, Kulbhushan; Das, Deepthy; Prasad, Babu Rajendra; Lakshmi, Sai (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Adenomatoid odontogenic tumor (AOT) is a rare tumor of epithelial origin which accounts for 3% of odontogenic tumors. The most common area of involvement is the maxilla, about 65% of cases, followed by the mandibular region accounting to 35% of cases. This case report is of a 16 year old girl operated and diagnosed with AOT at the anterior aspect of the mandible. This case report also discussed about the necessity for a detailed descriptive, differentiating features of AOT from other odontogenic tumors, the most common misdiagnosis being dentigerous cyst.